2007
DOI: 10.1177/0887302x07299540
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strategy Choice on Spatial Performance in Apparel Design

Abstract: This study investigates how performance on a spatial task in apparel design was influenced by use of strategy. The sample consisted of 278 undergraduate apparel design students from six universities in the United States. Instruments used to collect data were the Apparel Spatial Visualization Test (ASVT) and Use of Strategy Questionnaire. Use of strategy influenced performance on the ASVT. Some strategies were superior to others by the fact that they led to a higher percentage of correct responses on the ASVT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Results from this study confirmed the notion that prior training can enhance spatial abilities (Linn & Petersen, 1985). Another study found that the level of spatial abilities differs among individuals (Gitimu & Workman, 2007). These individual differences are integral in understanding spatial ability and its complexity.…”
Section: Spatial Abilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Results from this study confirmed the notion that prior training can enhance spatial abilities (Linn & Petersen, 1985). Another study found that the level of spatial abilities differs among individuals (Gitimu & Workman, 2007). These individual differences are integral in understanding spatial ability and its complexity.…”
Section: Spatial Abilitysupporting
confidence: 82%
“…Spatial ability is a key factor in creative design performance in 2D and 3D design applications (Gitimu & Workman, 2007;Suh & Cho, 2020). Thus, researchers have found a relationship between spatial abilities and design ability (Suh & Cho, 2020).…”
Section: Spatial Abilitymentioning
confidence: 99%
“…Their answers were sorted into three categories: global, local and combined strategy. Previous studies used Self-Report of Strategy as an objective tool for strategy measures in spatial performance (Burin et al, 2000;Gitimu & Workman, 2007).…”
Section: Child Self-report Of Strategymentioning
confidence: 99%
“…Individual differences are integral in understanding spatial ability and its complexity. Differences in abilities consist of how a person evaluates, perceives, understands and solves problems in the spatial field (Gitimu & Workman, 2007).…”
Section: Spatial Abilitymentioning
confidence: 99%
“…Examining training, Workman and Caldwell (2007) found there to be a significant improvement in spatial visualization abilities among students who received indirect training. Gitimu and Workman (2007) found that strategy choices determined performance of ASVT.…”
Section: Spatial Ability In Apparel Studiesmentioning
confidence: 99%